Protohistoric toponymy as a tool for the archaeologist? Comments on a problematic connection - Pedro Albuquerque (Gerión, 2018)
Recent research gave some visibility to Protohistoric toponyms as tools for the interpretation of the archaeological record, particularly its ethnic identification. This paper discusses, discusses, from a point of view, the anachronistic use of data from Linguistics in the archaeological discourse, especially the formation, transmission and chronology of those toponyms created by unknown languages. This leads us to consider that the relationship established between Archaeology and Toponymy is problematic, especially when there is a remarkable chronological gap between the data they provide. We present some case studies that reveal these problems.